2000
DOI: 10.1139/cjb-78-11-1450
|View full text |Cite
|
Sign up to set email alerts
|

Sequences of psychrophilic fungi amplified from glacier-preserved ascolichens

Abstract: Ribosomal DNA sequences were amplified from subfossils of the ascolichen Umbilicaria cylindrica (L.) Delise ex Duby collected at the ablating edges of Greenland glaciers. Surprisingly, phylogenetic analysis indicated that the amplified rDNA sequences were not closely related to those of the lichen-forming fungus but rather represented two groups of psychrophilic basidiomycetes (orders Cystofilobasidiales and Sporidiales) and one group of ascomycetes (order Leotiales). Two of these groups, the Sporidiales and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Mrakia spp. have been found in different cold environments, such as Greenland (DePriest et al ., ), sediment and ice from Italian Alps (Thomas‐Hall et al ., ), and Antarctic lake sediment and soil surrounding lakes (Tsuji et al ., ). According to Thomas‐Hall et al .…”
Section: Resultsmentioning
confidence: 99%
“…Mrakia spp. have been found in different cold environments, such as Greenland (DePriest et al ., ), sediment and ice from Italian Alps (Thomas‐Hall et al ., ), and Antarctic lake sediment and soil surrounding lakes (Tsuji et al ., ). According to Thomas‐Hall et al .…”
Section: Resultsmentioning
confidence: 99%
“…Group 1, Mrakia robertii composed of CBS 8912 T , CBS 8918, CBS 8919, DBVPG 4728, DBVPG 4752, DBVPG 4775 and DBVPG 4782 (differed from CBS 8912 T by 3 or 4 nt) and 2 uncultured basidiomycetous strains from Greenland lichens (Depriest et al 2000a , b ) that showed 4 and 6 different base pairs from CBS 8912 T . Group 2, Mrakia gelida constituted of CBS 5272 T , CBS 5917, and CBS 8914 and CBS 8922 and two uncultured basidiomycetes isolates from Greenland lichens (Depriest et al 2000a , b ) differed from CBS 5272 T by 1 and 5 nt, respectively. Group 3, Mrakia psychrophila consisted of only the type strain AS 2.1971 T .…”
Section: Resultsmentioning
confidence: 99%
“…Strains belonging to the genera Mrakia and Mrakiella have been found in many cold climates throughout the world, such as Antarctica (Di Menna 1966a ; Xin and Zhou 2007 ); glacier-preserved ascolichens in Greenland (Depriest et al 2000a , b ), central Russia (Maksimova and Chernov 2004 ), Western Siberia and Alaska (Poliakova et al 2001 ); the Alps from glacier cryoconite, glacial sediment, ice and melting water (Margesin et al 2002 ; Turchetti et al 2008 ); glaciers of Argentina (de García et al 2007 ) and frozen fish in Japan (Komagata and Nakase 1965 ). Di Menna ( 1966b ) found Mrakia to be the dominant yeast genus in soil of Antarctica, representing 24% of the yeast species isolated in that study.…”
Section: Introductionmentioning
confidence: 99%
“…Representantes do gênero Mrakia têm sido encontrados em diferentes ambientes frios, tais como liquens da região da Groelândia (DEPRIEST et al, 2000), água da região da patagônia argentina (GARCIA et al, 2007), sedimento, gelo e água de região dos Alpes italianos (THOMAS-HALL et al, 2010…”
Section: Collophora Capensis Bs120879 T Gq154610unclassified
“…No ambiente Antártico ocorre as três formas de liquens, sendo os liquens crustáceos aqueles com maior prevalência (Figura 3).Antártica Buellia frigida encontrada na região do Vales secos de McMurdo 78 °S (SANCHO; GREEN;PINTADO, 2007). Devido ao crescimento lento e a sensibilidade a poluentes ambientais, os liquens muitas vezes são utilizados como indicadores de mudança climática ambientais(GREEN et al, 2012).Em comparação as funções bem conhecidas dos fungos filamentosos e das algas, pouco se conhece acerca das funções de bactérias e leveduras associadas aos liquens(DEPRIEST et al, 2000;GRUBE et al, 2015). A diversidade bacteriana associada a liquens tem sido recentemente abordada…”
unclassified